Mitigasi Risiko dalam Perjanjian Pre-Project Selling terhadap Keadaan Memaksa (Force Majeure) - Wafi Adiyu Hibatullah; Anjar Sri Ciptorukmi Nugraheni (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the responsibility of developers and consumers in the pre-project selling agreement if force majeure occurs. And this research aims to analyze the actions or risk mitigation efforts that can be taken by developers and consumers in the pre-project selling agreement if a force majeure event occurs. The approach used is normative with statutory and comparative methods, relying on primary and secondary legal materials through literature studies. This research uses descriptive analysis, namely describing the impact of force majeure events on pre-project selling agreements that correlate with liability and risk mitigation efforts for developers and consumers. The liability of developers and consumers to risks due to force majeure is that developers and consumers are fully responsible for their rights and obligations in the agreement. Developers are responsible for providing clarity of information according to the agreement, while consumers are responsible for their own actions against risks according to the agreed agreement. Risk mitigation efforts that can be done by developers and consumers are setting force majeure clauses in pre-project selling agreements to protect the interests of developers and consumers and making addendums as an alternative solution that is preventive to legal risks in pre-project selling agreements.